2018
DOI: 10.1016/j.nrl.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la estimulación cerebral profunda en la carga de cuidadores de pacientes con enfermedad de Parkinson

Abstract: According to our results, treatment with DBS is not associated with lower caregiver burden. Apathy in patients and anxiety in caregivers are factors associated with the appearance of overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…19,20 This evidence was in line with the conclusions of another recent trial showing that treatment with DBS was not associated with a lower caregiver burden compared to treatment with other antiparkinsonian therapies. 21 Moreover, few data on the effect of apomorphine on caregiver burden are available. 18 In our previous report of the results from the PREDICT study, whose aim was to describe the burden of carers of advanced PD patients either treated with CSAI, LCIG, or continuing with their CU, we showed that caregiver burden tended to be lower when patients were treated with LCIG than with CU.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 This evidence was in line with the conclusions of another recent trial showing that treatment with DBS was not associated with a lower caregiver burden compared to treatment with other antiparkinsonian therapies. 21 Moreover, few data on the effect of apomorphine on caregiver burden are available. 18 In our previous report of the results from the PREDICT study, whose aim was to describe the burden of carers of advanced PD patients either treated with CSAI, LCIG, or continuing with their CU, we showed that caregiver burden tended to be lower when patients were treated with LCIG than with CU.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo antes mencionado, la calidad de vida en cuidadores de pacientes con EP presenta mayor relación de sobrecargaansiedad al ser alterados ejes económicos, emocionales y sociales 34 , siendo necesaria la intervención psicoterapéutica para mejorar las alteraciones en la calidad de vida de ambas partes 35 . Genç y col., en su estudio mencionado con anterioridad demostraron que un 40-50 % del binomio presentaban síntomas depresivos asociados a síntomas no motores y eran incrementados por la fatiga, acrecentando a su vez la dependencia.…”
Section: Calidad De Vida De Los Cuidadoresunclassified
“…The quality of life of patients with PD decreases considerably due to changes in both motor and non-motor functions. The resulting functional disability places a considerable physical and mental burden on family members and caregivers [ 5 ]. The clinical manifestations of PD are characterized by slow movements, resting tremor and rigidity, together with non-motor manifestations.…”
Section: Introductionmentioning
confidence: 99%